Outcomes and risk factors for failed trial of labor after cesarean delivery (TOLAC) in women with one previous cesarean section: a Chinese population-based study - Xiaobo He; Qiaona Dai; Xiaoli Wu; Junjun Zhou; Jie Li (BMC, 2022)
Abstract Objective To evaluate the outcomes and risk factors for trial of labor after cesarean delivery (TOLAC) failure in patients in China. Methods Consecutive patients who had a previous cesarean delivery (CD) and attempted TOLAC were included from 2014 to 2020. Patients who successfully delivered were classified into the TOLAC success group. Patients who attempted TOLAC but had a repeat CD due to medical issues were classified into the TOLAC failure group. Multiple logistic regression analyses were performed to examine the risk factors for TOLAC failure. Results In total, 720 women who had a previous CD and attempted TOLAC were identified and included. The success rate of TOLAC was 84.2%(606/720). Seven patients were diagnosed with uterine rupture, none of whom underwent hysterectomy. Multiple logistic regression analysis showed that the induction of labor (OR = 2.843, 95% CI: 1.571-5.145, P < 0.001) was positively associated with TOLAC failure, but the thickness of the lower uterine segment (LUS) (OR = 0.215, 95% CI: 0.103-0.448, P < 0.001) was negatively associated with TOLAC failure. Conclusions This study suggested that TOLAC was effective in decreasing CD rates in the Chinese population. The induction of labor was positively associated with TOLAC failure, but the thickness of the LUS was negatively associated with TOLAC failure. Our findings need to be confirmed in larger samples with patients of different ethnicities.